2004
DOI: 10.2960/j.v35.m527
|View full text |Cite
|
Sign up to set email alerts
|

Age, Growth and Maturity of the Commercial Ray Species from the Irish Sea

Abstract: The age, growth and maturity of 1 554 individuals (268 Raja brachyura, 258 R. clavata, 468 R. montagui and 560 Leucoraja naevus) of the main commercial ray species from the Irish Sea were determined from samples taken from commercial and research trawls between 1997 and 1998. Sagittal sections of vertebral centra stained using crystal violet enhanced the underlying band patterns of each species, allowing the derivation of age and von Bertalanffy growth parameters. Age estimates were relatively low for each spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
40
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 14 publications
11
40
0
1
Order By: Relevance
“…This characteristic is a common feature in elasmobranchs where females reach a greater size and weight than males (Braccini & Chiaramonte 2002) as found in Leucoraja wallacei and Dipturus pullopunctatus (Walmsley-Hart et al 1999) where females grow larger but more slowly than males. A similar feature was described also by Gallagher et al (2004) for several rajid species in the Irish Sea, including the blonde ray where the growth rates found in males were higher than that found in females (male: K50.145; female: K50.129). The larger size and age at maturity reached by female rajids is probably related to different reproductive strategies between sexes (Walmsley-Hart et al 1999).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…This characteristic is a common feature in elasmobranchs where females reach a greater size and weight than males (Braccini & Chiaramonte 2002) as found in Leucoraja wallacei and Dipturus pullopunctatus (Walmsley-Hart et al 1999) where females grow larger but more slowly than males. A similar feature was described also by Gallagher et al (2004) for several rajid species in the Irish Sea, including the blonde ray where the growth rates found in males were higher than that found in females (male: K50.145; female: K50.129). The larger size and age at maturity reached by female rajids is probably related to different reproductive strategies between sexes (Walmsley-Hart et al 1999).…”
Section: Discussionsupporting
confidence: 57%
“…The high age at maturity reported for the blonde ray (Tm year59, f540; Frisk et al 2001) was generally confirmed by the large size at maturity for males (Gallagher et al 2004). This aspect, with low fecundity values and low growth rates, reflects the high vulnerability of R. brachyura to fishing activities and it needs to be considered in management and conservation strategies (Holden 1973(Holden , 1974Compagno 1990;Hoenig & Gruber 1990).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Studies on the biology of this species have been carried out mainly in the north-eastern Atlantic Ocean. They have focused on growth rates and ageing (Holden, 1972;Fahy, 1991;Gallagher et al, 2005;Serra-Pereira et al, 2005a), conversion factors (Dorel, 1986;Serra-Pereira et al, 2010;McCully et al, 2012), some reproductive aspects (Clark, 1922;Holden et al, 1971;Gallagher et al, 2005;McCully et al, 2012) and diet (Holden & Tucker, 1974;Quiniou & Rabarison Andriamirado, 1979;Ajayi, 1982;Ellis et al, 1996;. However, information on its general biology in the Mediterranean is very limited.…”
Section: Introductionmentioning
confidence: 99%